Long wavelength-sensing cones of zebrafish retina exhibit multiple layers of transcriptional heterogeneity - Farre, Ashley A.; Sun, Chi; Starostik, Margaret R.; Hunter, Samuel S.; English, Milton A.; Duncan, Audrey; Santhanam, Abirami; Shihabeddin, Eyad; O’Brien, John; Swaroop, Anand; Stenkamp, Deborah L. (Frontiers in Cellular Neuroscience, 2023)
Introduction: Understanding how photoreceptor genes are regulated is important for investigating retinal development and disease. While much is known about gene regulation in cones, the mechanism by which tandemly-replicated opsins, such as human long wavelengthsensitive and middle wavelength-sensitive opsins, are differentially regulated remains elusive.In this study, we aimed to further our understanding of transcriptional heterogeneity in cones that express tandemly-replicated opsins and the regulation of such differential expression using zebrafish, which express the tandemly-replicated opsins lws1 and lws2.Methods: We performed bulk and single cell RNA-Seq of LWS1 and LWS2 cones, evaluated expression patterns of selected genes of interest using multiplex fluorescence in situ hybridization, and used exogenous thyroid hormone (TH) treatments to test selected genes for potential control by thyroid hormone: a potent, endogenous regulator of lws1 and lws2 expression.Our studies indicate that additional transcriptional differences beyond opsin expression exist between LWS1 and LWS2 cones. Bulk RNA-Seq results showed 95 transcripts enriched in LWS1 cones and 186 transcripts enriched in LWS2 cones (FC>2, FDR<0.05). In situ hybridization results also reveal underlying heterogeneity within the lws1-and lws2-expressing populations. This heterogeneity is evident in cones of mature zebrafish, and further heterogeneity is revealed in transcriptional responses to TH treatments. Discussion: We found some evidence of coordinate regulation of lws opsins and other genes by exogenous TH in LWS1 vs LWS2 cones, as well as evidence of gene regulation not mediated by TH. The transcriptional differences between LWS1 and LWS2 cones are likely controlled by multiple signals, including TH.